Dual effects of reversed winter–spring temperatures on year‐to‐year variation in the recruitment of chub mackerel (Scomber japonicus). (8th November 2018) - Kaneko, Hitoshi; Okunishi, Takeshi; Seto, Takashi; Kuroda, Hiroshi; Itoh, Sachihiko; Kouketsu, Shinya; Hasegawa, Daisuke
Abstract: To clarify the effects of temperature on the recruitment of chub mackerel ( Scomber japonicus ) in the North Pacific, we investigated the influence of winter surface temperature (WST) on spawners at the time of maturity around the spawning grounds and the influence of ambient spring temperature on larvae using estimated temperature (ET) obtained from particle tracking experiments. We found a significant positive correlation between ET approximately 10 days following hatching and the recruitment per spawning stock biomass (RPS) after 2000. The closer (more meandering) the Kuroshio Current (KC) axis was in relation to the spawning ground, the higher (lower) the spring surface temperature and the higher (lower) RPS was in the spawning ground. In contrast, WST inside KC near the maturity/spawning ground was significantly negatively correlated with RPS. A significant negative correlation between the temperatures in winter and spring was detected in the area after 2000, when the conditions of the Pacific decadal oscillation index and the stability of the Kuroshio Extension were synchronous, indicating that KC shifted northward during this time. The reversed temperature pattern was consistent with the winter–spring movement of KC axis in the offshore direction and was correlated with the winter–spring difference in the intensity of the Aleutian low. These results suggest that the annual variation in chub mackerel recruitment after 2000 was strongly affected by the combined effects of ambient temperature because of the reversal of conditions that occurred between winter and spring around the maturity/spawning ground, which was related to the KC path.